2021
DOI: 10.3390/en14196167
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation and Wind Tunnel Investigation on Static Characteristics of VAWT Rotor Starter with Lift-Drag Combined Structure

Abstract: In order to get rid of the impact of the global financial crisis and actively respond to global climate change, it has become a common choice for global economic development to develop clean energy such as wind energy, improve energy efficiency and reduce greenhouse gas emissions. With the advantages of simple structure, unnecessary facing the wind direction, and unique appearance, the vertical axis wind turbine (VAWT) attracts extensive attention in the field of small and medium wind turbines. The lift-type V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Therefore, the combined design of the Savonius and Darrieus wind turbines can improve the energy capture performance of the Darrieus wind turbines, especially in a low wind speed environment. Fang Feng designed a VAWT with a combination of lift and drag and studied in detail the impact of blade number changes on the performance of the VAWT through a combination of CFD simulation and experiments [18]. The research results indicate that the lift-drag hybrid wind turbine with three blades has the best static starting characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the combined design of the Savonius and Darrieus wind turbines can improve the energy capture performance of the Darrieus wind turbines, especially in a low wind speed environment. Fang Feng designed a VAWT with a combination of lift and drag and studied in detail the impact of blade number changes on the performance of the VAWT through a combination of CFD simulation and experiments [18]. The research results indicate that the lift-drag hybrid wind turbine with three blades has the best static starting characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Hosseini et al [22] modeled and analyzed a hybrid VAWT and showed that the hybrid wind turbine has a good self-starting ability, and the maximum utilization rate of wind energy is 48.4% when the tip speed ratio is 2.5. In order to improve the starting performance of lift-drag composite VAWTs, Fang Feng et al [23] designed a lift-drag composite starter for lift-drag vertical-axis wind turbines.…”
Section: Introductionmentioning
confidence: 99%